The Impacts of Chemopoly-Edutainment to Learning Activities and Responses - Sri Adelila Sari; Jasmidi Jasmidi; Agus Kembaren; Ajat Sudrajat (Intelektual Pustaka Media Utama, 2018)
The purpose of this study was to alleviate the problem of student learning activities through the use of innovative chemistry learning media, namely chemopoly-edutainment. This type of research was a pre-experimental study. The approach used was descriptive qualitative approach. This research has been done in Medan State University in 2017 year. The selection of research subjects was done by purposive sampling, i.e., Chemistry Department students as many as 36 people. Data were collected using observation sheet to measure learning activities. Then, students' responses were measured using a questionnaire. The results showed that learning about chemicals separation by using chemopoly-edutainment media could help students to be more active in learning. The activeness of students in the highly active category was found at 77.16 percent. While active students learn was reached 20.68 percent. In addition, found as many as 2.16 percent of students who were quite active. The study also found that none of the students were less active or inactive in teaching and learning activities using the chemopoly-edutainment medium. The students’ responses to the use of chemopoly-eudtainment media on chemical separation learning was also found to be positive.